Fictionalising interpreters: traitors, lovers and liars in the conquest of America - Ríos Castaño, Victoria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Conquistadors’ interpreters in America could be seen as mediators whose effort made possible the communication between Indians and Europeans. Yet, their very names are stigmatised as symbols of betrayal if and when they emerge as fictionalised figures in literature, political move-ments and popular culture. Columbus’ interpreter is an outcast in both the New and the Old World. La Malinche is widely epitomised as Cortés’ mis-tress and traitor of the Aztecs, although her identity has been re-evaluated as mother of the Mexican nation and feminist icon of Chicana writers. Felipillo, Pizarro ’s ill-reputed interpreter, is used in the Andean regions as a metaphor for corrupt politicians.